2014
DOI: 10.1162/neco_a_00659
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Benefits Symptoms in Gulf War Veterans: Results of a Randomized Double-Blind Study

Abstract: We sought to assess whether coenzyme Q10 (CoQ10) benefits the chronic multisymptom problems that affect one-quarter to one-third of 1990-1 Gulf War veterans, using a randomized, double-blind, placebo-controlled study. Participants were 46 veterans meeting Kansas and Centers for Disease Control criteria for Gulf War illness. Intervention was PharmaNord (Denmark) CoQ10 100 mg per day (Q100), 300 mg per day (Q300), or an identical-appearing placebo for 3.5 ± 0.5 months. General self-rated health (GSRH), the prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 234 publications
(230 reference statements)
1
38
0
Order By: Relevance
“…The lack of any effect on pain was an unexpected result. Although pain response in CFS patients has not been previously analyzed, a possible effect of CoQ 10 or NADH on pain perception has been suggested in other pathologies such as fibromyalgia [31]. In view of the study's design, any description of the mechanisms underlying the results would be purely speculative and would need to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The lack of any effect on pain was an unexpected result. Although pain response in CFS patients has not been previously analyzed, a possible effect of CoQ 10 or NADH on pain perception has been suggested in other pathologies such as fibromyalgia [31]. In view of the study's design, any description of the mechanisms underlying the results would be purely speculative and would need to be confirmed in future studies.…”
Section: Discussionmentioning
confidence: 96%
“…Dysfunctions in these two coenzymes have also been associated with neurodegenerative diseases and cancer [29,30]. CoQ 10 and NADH deficiencies have also been described in patients with CFS and fibromyalgia [9,12,31], and it has also been suggested that serum NADH levels are directly correlated with serum CoQ 10 concentration in these patients. Several components of the mitochondrial system require diet replacement and this need can be facilitated with natural nutritional supplements [13].…”
Section: Discussionmentioning
confidence: 99%
“…Although, at present there is a paucity of information available on the therapeutic efficacy of CoQ 10 in the treatment of the clinical symptoms associated with OP poisoning in human subjects. However, veterans suffering with Gulf War syndrome, a condition associated with OP poisoning, have been reported to show some clinical improvement following CoQ 10 treatment [30]. The factors responsible for biochemical and clinical efficacy of CoQ 10 in the treatment of OP toxicity have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Cure-all treatments for GWI do not currently exist due, in part, to GWI’s complexity; however, experimental therapeutic interventions have provided benefits to some GWI symptoms [ 33 , 34 , 35 , 36 ]. Current treatments for GI disorders in general, include altering diet and/or lifestyle, probiotic supplementation, and fecal microbiota transplants; some have been beneficial to patients with neurological disorders including PD, Multiple Sclerosis, and Alzheimer’s Disease [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%